Gene and protein expression of oestrogen-beta and progesterone receptors in facial melasma and adjacent healthy skin in women - Tamega, A. de A. [UNESP]; Miot, H. A. [UNESP]; Moco, N. P. [UNESP]; Silva, M. G. [UNESP]; Marques, M. E. A. [UNESP]; Miot, L. D. B. [UNESP] (Wiley-Blackwell, 2015)
SynopsisObjectiveCompare gene and protein expression for oestrogen receptor- (ER-) and progesterone receptor (PR) in facial melasma and adjacent healthy skin.MethodsA cross-sectional study including 42 women with facial melasma, conducted at the Dermatology Service of Botucatu Medical School of SAo Paulo State University, Brazil. Biopsies of the melasma skin were performed, together with healthy surrounding skin. The gene expression (real-time PCR) of the hormone receptors in the tissue was evaluated. Subsequently, skin fragments were immunostained for nuclear ER- and PR, evaluated according to their HSCORE (epidermis) and percentage of staining per microscopic field (dermis).ResultsMessenger RNA tissue expression for ER- and PR showed no difference between melasma-affected skin fragments and the healthy perilesional areas (P>0.2). Median nuclear epithelial expression for ER- and PR was higher in lesioned skin (HSCORE 157 and 58) than in the healthy perilesional skin (HSCORE 97 and 19; P<0.01), with no difference in dermal immunostaining. Nuclear histological expression for ER- was associated to sun-induced melasma and negative familiar background; PR expression was associated to sun-induced melasma and darker phototypes.ConclusionNo difference was observed in gene expression for oestrogen- and progesterone receptors in melasma-affected skin compared with adjacent healthy skin. However, the higher protein expression of these receptors in melasma-affected epithelia suggests hormonal participation in the pathogenesis of this disease.
Keywords: immunohistochemistry; melanin; melanocytes; melanogenesis; melasma; oestrogen receptor-; pigmentation; progesterone receptor